2011
DOI: 10.1163/22941932-90000058
|View full text |Cite
|
Sign up to set email alerts
|

The use of near Infrared Spectroscopy to Identify solid wood Specimens of Swietenia Macrophylla0 (Cites Appendix II)

Abstract: Near infrared spectroscopy (NIRS) has been shown effective as a tool for identifying Swietenia when tested as laboratory-processed powder, but testing such powdered wood is not readily adaptable to the fieldidentification of wood. This study explored the efficacy of a fiber optic NIRS scan of solid wood surfaces to separate Swietenia macrophylla King, Carapa guianensis Aubl., Cedrela odorata L., and Micropholis melinoniana Pierre. Transverse, radial, and tangential surfaces were scanned to determine if the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 30 publications
0
40
0
4
Order By: Relevance
“…These tools can be used to verify the claimed timber species and its geographic origin at discrete points along the supply chain from a logged forest to the point of sale [9]. The identity of timber species can be verified on the basis of wood anatomy [10], metabolic profiles [11], near-infrared spectroscopy [12] and DNA barcoding [13]. Geographic origin along the timber supply chain can be verified by tree rings [14], stable isotopes [15] and population structure [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…These tools can be used to verify the claimed timber species and its geographic origin at discrete points along the supply chain from a logged forest to the point of sale [9]. The identity of timber species can be verified on the basis of wood anatomy [10], metabolic profiles [11], near-infrared spectroscopy [12] and DNA barcoding [13]. Geographic origin along the timber supply chain can be verified by tree rings [14], stable isotopes [15] and population structure [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 13 The concentrations of holocellulose (cellulose+hemicellulose), lignin and extractives obtained using the conventional wet chemistry methods are shown in Table 1. These results were used as the average or global concentration for the wood sample.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[7]. In wood and wood-based materials, the rapid assessment of the chemical composition using NIR in applications related to the quality has provided an increasing number of publications for industrial applications in this area [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Adedipe et al [26] reported an automatic algorithm for discrimination of two oak species (white and red oak) on the basis of NIR spectra. Pastore et al [27] and Braga et al [28] used NIR for determination of exotic wood species. Corresponding results were obtained by Wienhaus et al [29] but applying mid IR spectroscopy.…”
Section: Recognition Of Wood Species and Provenancementioning
confidence: 99%